2020
DOI: 10.1103/physrevmaterials.4.015801
|View full text |Cite
|
Sign up to set email alerts
|

Polar or not polar? The interplay between reconstruction, Sr enrichment, and reduction at the La0.75Sr0.25MnO3 (001) surface

Abstract: Perovskite oxides used in heterogeneous catalysis and electrocatalysis are tuned by substitutional doping. Sr-doped LaMnO 3 is a popular choice of electrode material for electrochemical energy conversion. At elevated temperatures, relevant to solid oxide fuel or electrolysis cells, Sr enriches at the surface, which leads to fast degradation of the oxygen exchange activity at the surface. In this work, we investigate the effect of oxygen partial pressure p(O 2) and temperature on Sr segregation at the La 0.75 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 87 publications
(123 reference statements)
3
22
0
Order By: Relevance
“…Particularly critical for the operation of solid-oxide fuel cells is the widely reported segregation of Sr-rich phases under operating conditions, which tends to degrade the oxygen exchange activity at the surface. 89 Sr segregation and the formation of insulating Sr-rich clusters is a very common phenomenon observed in LSMO and other perovskite oxides under conditions comparable to those employed in this work, 26,70 and it has been widely investigated, both experimentally and theoretically. 27,89 Notably, the lms presented in this work do not show this phenomenon.…”
Section: Origin Of the Surface Reconstructionsmentioning
confidence: 93%
See 2 more Smart Citations
“…Particularly critical for the operation of solid-oxide fuel cells is the widely reported segregation of Sr-rich phases under operating conditions, which tends to degrade the oxygen exchange activity at the surface. 89 Sr segregation and the formation of insulating Sr-rich clusters is a very common phenomenon observed in LSMO and other perovskite oxides under conditions comparable to those employed in this work, 26,70 and it has been widely investigated, both experimentally and theoretically. 27,89 Notably, the lms presented in this work do not show this phenomenon.…”
Section: Origin Of the Surface Reconstructionsmentioning
confidence: 93%
“…89 Sr segregation and the formation of insulating Sr-rich clusters is a very common phenomenon observed in LSMO and other perovskite oxides under conditions comparable to those employed in this work, 26,70 and it has been widely investigated, both experimentally and theoretically. 27,89 Notably, the lms presented in this work do not show this phenomenon. XPS does not indicate any substantial deviation of the La-to-Sr ratio from the nominal composition in the near-surface region.…”
Section: Origin Of the Surface Reconstructionsmentioning
confidence: 93%
See 1 more Smart Citation
“…[25][26][27][28] The enrichment of dopants near the surface has recently been explained by a density functional theory (DFT)-based ab initio thermodynamics model of La 0.75 Sr 0.25 MnO 3 (LSM25) in our recent work. 29 We demonstrated that the surface free energy under SOFC operating conditions is minimized by a surface configuration with oxygen vacancies, whose positive relative charge is balanced by enriched dopants of relative negative charge, still within the perovskite surface lattice. Dopantrich phase precipitation, on the other hand, was predicted to occur only under SOEC operating conditions (anodic polarization), but not under SOFC operating conditions (cathodic polarization).…”
Section: Introductionmentioning
confidence: 87%
“…In this way, the impedance response is dominated by the thin-film cathode [54]. b) as determined below, the as-grown VAN film is under out-of-plane tension: such tensile strain is known to induce Sr surface segregation [38,57], resulting in electronically and ionically insulating Sr-enriched phases, which severely impedes surface oxygen exchange [58]. [59] An outof-plane tension in the as-grown VAN film is expected because of the presence of stiff, and larger lattice parameter MgO cf.…”
Section: Fig 2(g)mentioning
confidence: 99%